Odpowiedź :
1.
[tex] \frac{2x + 3} {5} = \frac{2 - x}{3} - x[/tex]
[tex]3(2x + 3) = 5(2 - x) - 45[/tex]
[tex]6x + 9 = 10 - 5x - 45[/tex]
[tex]6x + 9 = - 35 - 5x[/tex]
[tex]6x + 5x = - 35 - 9[/tex]
[tex]11x = - 44[/tex]
[tex]x = - 4[/tex]
2.
[tex] \frac{x + 1}{2} - \frac{x - 1}{3} = \frac{1}{4} [/tex]
[tex]6(x + 1) - 4(x - 1) = 3[/tex]
[tex]6x + 6 - 4x + 4 = 3[/tex]
[tex]2x + 10 = 3[/tex]
[tex]2x = 3 - 10[/tex]
[tex]2x = - 7[/tex]
[tex]x = - \frac{7}{2} = 3 \frac{1}{2} [/tex]
3.
[tex] \frac{4x + 7}{2} - \frac{5x - 1}{6} = x + 5[/tex]
[tex]3(4x + 7) - (5x - 1) = 6x + 30[/tex]
[tex]12x + 21 - 5x + 1 = 6x + 30[/tex]
[tex]7x + 22 = 6x + 30[/tex]
[tex]7x - 6x = 30 - 22[/tex]
[tex]x = 8[/tex]
4.
[tex] \frac{x + 5}{4} - \frac{2x + 1}{8} = \frac{1}{2} \times (2 - x)[/tex]
[tex] \frac{x + 5}{4} - \frac{2x + 1}{8} = 1 - \frac{1}{2} x[/tex]
[tex]2(x + 5) - (2x + 1) = 8 - 4x[/tex]
[tex]2x + 10 - 2x - 1 = 8 - 4x[/tex]
[tex]10 - 1 = 8 - 4x[/tex]
[tex]9 = 8 - 4x[/tex]
[tex]4x = 8 - 9[/tex]
[tex]4x = - 1[/tex]
[tex]x = - \frac{1}{4} \: lub \: 0.25[/tex]
Mam nadzieję że pomogłam ❤️